Functionalization of micropipette tips with hydrophobin-laccase chimera and application to the electrochemical determination of caffeic acid in tea samples. (April 2023) - Stanzione, Ilaria; Pennacchio, Anna; Piscitelli, Alessandra; Giardina, Paola; Costa-Rama, Estefanía; Fernández-Abedul, M. Teresa
Abstract: Performing on-site measurements is one of the main challenges of current (bio)chemical analysis. Micropipette tips, which are among the most common utilities in laboratories, can be useful and cheap elements for designing out-of-the-box innovative analytical biodevices. Furthermore, most of the analytical properties of these bioplatforms depend on the immobilization of the recognition element (e.g., enzymes). In this context, we have recently designed a chimeric protein in which laccase PoxA1b from the fungus Pleurotus ostreatus has been genetically fused to the class I hydrophobin Vmh2. The ability to self-assemble at hydrophobic-hydrophilic interfaces of hydrophobin, allows an easy laccase immobilization. In this work, the Vmh2-PoxA1b fusion protein was immobilized into common polypropylene micropipette tips to develop an innovative enzymatic bioplatform that can produce fast results in a simple way. As proof of applicability, the platform was applied to the determination of caffeic acid by enzymatic oxidation and further electrochemical reduction of the product on a screen-printed electrode, achieving a limit of detection of 1.4·10 −6 M. It was then used for determining caffeic acid in tea samples. Graphical abstract: Image 1 Highlights: A fusion protein, laccase-hydrophobin, is immobilized on micropipette tips. A 1-min in-the-tip enzymatic reaction is enough for further electroanalysis. The use of a chimeric protein improves laccase immobilization on polypropylene tips. The product of the in-tip caffeic acid-laccase reaction is detected electrochemically. Laccase-based micropipette tips and miniaturized electrodes help decentralize analysis.